2022
DOI: 10.1007/s13555-021-00644-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposome and Skin. Part 2. The Influential Role of the Exposome, Beyond UVR, in Actinic Keratosis, Bowen’s Disease and Squamous Cell Carcinoma: A Proposal

Abstract: Actinic keratosis (AK) is the main risk factor for the development of cutaneous invasive squamous cell carcinoma (SCC). It represents the first sign of severe chronic ultraviolet radiation exposure, which has a clear significant effect. Nevertheless, the skin is exposed to many other exposome factors which should be thoroughly considered. Our aim was to assess the impact of exposome factors other than ultraviolet radiation (UVR) on the etiopathology of AK and Bowen's disease (BD) and progression of AK to SCC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 161 publications
0
4
0
1
Order By: Relevance
“…Frequent exposure to carcinogenic substances was linked to the significantly increased risk of SCC development. In certain professions, occupational or environmental exposure to carcinogens may contribute to the initiation and progression of SCC lesions 22 . In high‐risk environments, enhanced safety measures and stringent regulations are required to reduce exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent exposure to carcinogenic substances was linked to the significantly increased risk of SCC development. In certain professions, occupational or environmental exposure to carcinogens may contribute to the initiation and progression of SCC lesions 22 . In high‐risk environments, enhanced safety measures and stringent regulations are required to reduce exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Выживание Propionibacterium, обычной бактерии, колонизирующей кожу при акне, зависит от выработки кожного сала, и уменьшение ее присутствия может усугубить тяжесть высыпаний вследствие нарушения гомеостаза микробиома и стимулирования роста S. aureus [9]. И наоборот, S. aureus может быть причиной прогрессирования AK и трансформации АК в ПКРК посредством индукции хронического воспаления с выработкой оксида азота и цитокинов, которые способствуют канцерогенезу [11].…”
Section: микробиом при актиническом кератозе и злокачественных новооб...unclassified
“…PM causes inflammation in the skin through increased IL-8, MMP-1, ROS production, and neutrophil infiltration in the deep dermis [ 104 ]. Fibroblasts cultivated with conditioned medium obtained from immortalized human keratinocytes (HaCaT) treated with PM displayed increased nuclear translocation of p65 and p50 as well as increased ROS production, morphological changes, and secretion of SASP components including prostaglandin E2, COX-2, TNF-α, IL-1β, and IL-6 [ 93 ].…”
Section: Major Components Of Air Pollution Affecting Skin Appearancementioning
confidence: 99%
“…A report has shown that in human keratinocytes, exposure to ozone leads to lactate dehydrogenase release, reduced cell proliferation, lipid peroxidation, and NF-κB activation and these effects can be prevented by pretreatment with antioxidant mixtures [ 123 ]. Another study has shown that the combination of UVA and ozone has a synergistic effect and causes increased oxidative stress of the skin and Nrf2 expression in keratinocytes leading to skin inflammation, formation of wrinkles, and pigment spots [ 8 , 9 , 104 ]. In human skin O 3 leads to activation of NF-κB, MMP-9, COX-2, and lipid peroxidation in the epidermis, whereas in the dermis expression of collagen-1 and -3 are downregulated.…”
Section: Major Components Of Air Pollution Affecting Skin Appearancementioning
confidence: 99%